2022
DOI: 10.1186/s12957-022-02749-1
|View full text |Cite|
|
Sign up to set email alerts
|

Periosteal preservation: a new technique in resection of bone high-grade malignant tumors in children—about eleven cases

Abstract: Objective The purpose of this study was to describe a surgical technique of bone resection with periosteal preservation and reconstruction in patients with high-grade bone malignant tumors and to determine its effect on local recurrences, and time and quality of bone union in bone autografting reconstruction. Patients and methods We retrospectively reviewed 11 cases of high-grade malignant bone tumors in children aged 4 to 16 years, who were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Infection is another issue in need of attention because deep infection may cause implant failure and can even be life-threatening [ 41 ]. Enlonged operation time, immune-compromising management, and limited soft tissue coverage were related to the infections in patients with malignancies [ 42 , 43 ]. In this study, only a patient occured delayed wound healing without any deep infection and recovered after continuous dressing changing.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is another issue in need of attention because deep infection may cause implant failure and can even be life-threatening [ 41 ]. Enlonged operation time, immune-compromising management, and limited soft tissue coverage were related to the infections in patients with malignancies [ 42 , 43 ]. In this study, only a patient occured delayed wound healing without any deep infection and recovered after continuous dressing changing.…”
Section: Discussionmentioning
confidence: 99%
“…For all these trials, there are only two main types of OS: soft and solid, as observed in the table. The following active pharmaceutical ingredients (API) are appropriate for OS: topotecan (Tpt) [45], pazopanib (Pzp) [46], placebo (Plb) [47], gemcitabine (Gct) [48], M6620 [49][50], regorafenib (Rgf) [51][52], glembatumumab vedotin (GV) [53][54], lenvatinib [55], etoposide and ifosfamide (EnI) [56], nab-rapamycin (Rpm) [57][58], cyclophosphamide (Cfa) [59], simvastatin (Sim) [60], myeloid growth factor (MGF) [61], nab-paclitaxel [62][63], methotrexate (Mtx) [64], and doxorubicin (Dox) [65]. Besides, the primary tests, such as laboratory biomarker analyses [66] and dose escalation studies [67], were conducted for these successful triumphs.…”
Section: Clinical Advancementmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the author reported that the arrows, chevron and stars in Figs. 1 and 2 were removed during the corrections stage.…”
mentioning
confidence: 99%